แนวทางการพัฒนาอาจารย์เพื่อเตรียมความพร้อมในการสอนออนไลน์แบบเปิด สำหรับมวลชนในสถาบันอุดมศึกษา - ธรรมเมธา, ฐาปนีย์ (Journal of Education Studies, Chulalongkorn University, 2019)
This study of faculty development guidelines for Massive Open Online Course (MOOC) teaching readiness in Higher Education Institutes (HEIs) aimed to (1) investigate the existing conditions of teaching MOOCs in Thailand, (2) propose faculty development guidelines for teaching readiness in MOOCs, and (3) evaluate faculty development guidelines for teaching readiness in MOOCs.The instruments comprised a survey to examine existing conditions, a survey to examine needs, and an evaluation form to assess proposed guidelines. The results focused on four areas: (1) the existing conditions of MOOCs in HEIs, (2) the needs of MOOCs in HEIs, (3) the guidelines for MOOC teaching, and (4) the evaluation results of the proposed guidelines for MOOC teaching were presented for further implementation in HEIs.